(untitled) (Research, Society and Development, 2020)
Objective: To provide knowledge and clarify doubts about male breast cancer, advise on risks, show the technique of breast self-examination, in addition to stressing the importance of men touching and observing their breasts. Methodology: This is the description of an experience report lived at a Federal Institute of Education, Science and Technology of Maranhão in October 2019, male employees. The action was systematized following the model of theoretical and practical process by Backes et al. (2012). For data analysis and description of this experience report, Holliday’s concept was based (2006), following the steps Starting point, Initial questions, Recovery of the lived process, Reflection, Points of arrival. Results and Discussion: Most of the servers were in the 30-40 year age range, corroborating data from a study carried out in the Triângulo Mineiro region with teaching professionals from a Federal Institute in which they observed the prevalence of professionals in the age group of 31 to 40 years. Age represents a significant factor with regard to some cancers, being equally relevant in male breast cancer that is associated with older ages and with the possibility of being related to other co-morbidities. Asked if they had heard about male breast cancer, most men reported not having knowledge. Similar data were also found in a survey that, when questioned about the study participants’ knowledge about male breast cancer, 77.4% did not know this type of neoplasm. Final Considerations: Many men do not pay attention to the possibility of developing the disease, or even are unaware of this possibility, as was noticed in the data investigated during the intervention.